Meningkatkan Kecerdasan Moral Pada Anak Usia 5-6 Tahun Melalui Media Video Pembelajaran di TK Ananda Cianjur - Siti Nurfalah (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This article is a literature review that discusses moral education in early childhood which can be done through habituation, insertion of moral values in the teaching materials as well as imitation by children of the behavior and habits of adults around them. Because the low quality of children's morals will have a negative impact on their future, especially in the current era of modernization with very sophisticated technological developments. One of the efforts made by researchers to improve moral intelligence in children is by applying learning video media to children in stimulating moral development. This type of research is CAR with the Kemmis & Mc Taggart cycle model developed by Kurt Lewin. This research will be conducted for six months at Ananda Cianjur Kindergarten. With subjects taken children aged 5-6 years at Ananda Cianjur Kindergarten, a total of 20 people consisting of 8 girls and 12 boys. A sample will be taken for 4 girls and 6 boys. Data collection techniques are observation and documentation, with data analysis techniques of data reduction, data presentation and drawing conclusions.